Anti-citrullinated protein antibody positivity correlates with cartilage damage and proteoglycan levels in patients with rheumatoid arthritis in the hand joints - Renner, Nina; Krönke, Gerhard; Rech, Jürgen; Uder, Michael; Janka, Rolf Matthias; Lauer, Lars; Paul, Dominik; Herz, Barbara; Schlechtweg, Philipp; Hennig, Friedrich; Schett, Georg; Welsch, Götz (Arthritis and Rheumatology, 2014)
Objective: To investigate the factors associated with cartilage proteoglycan content in patients with rheumatoid arthritis (RA) Methods: 32 RA patients received high-field 3 Tesla Gadolinium-Enhanced MRI of Cartilage (dGEMRIC) for determining cartilage proteoglycan content. Measurements were performed in three individual cartilage regions (medial, central, lateral) of the metacarpophalangeal joints 2 and 3. dGEMRIC values were then related to disease duration, disease activity, anti-citrullinated protein antibody (ACPA) status, rheumatoid factor status and C-reactive protein level. Results: dGEMRIC values were not significantly different between the MCP2 and MCP3 joint. Inter-class correlations were high (>0.92) for all three (medial, central and lateral) cartilage compartments. dGEMRIC values were significantly lower in RA patients with longer disease duration (>=3 years) and those with ACPA positivity than those with a short disease duration (<3 years)(p=0.034) or negative ACPA (p=0.0002), respectively. In contrast, no association between cartilage proteoglycan content and disease activity, C-reactive protein level and rheumatoid factor status was found. Conclusion: Decreased cartilage proteoglycan content in RA patients is associated with disease duration and ACPA positivity but not with the actual disease activity, CRP level or rheumatoid factor status. These data suggest that the cumulative burden of inflammation as well as ACPA are the determinants for cartilage damage in RA.
EVALuna2:12983

Osteitis and synovitis, but not bone erosion, is associated with proteoglycan loss and microstructure damage in the cartilage of patients with rheumatoid arthritis - Herz, Barbara; Albrecht, Andreas; Englbrecht, Matthias; Welsch, Götz; Uder, Michael; Renner, Nina; Schlechtweg, Philipp; Paul, Dominik; Lauer, Lars; Engelke, Klaus; Janka, Rolf Matthias; Rech, Jürgen; et al. (Annals of the Rheumatic Diseases, 2014)
To investigate the relation between anatomic changes of the synovium, the bone, the bone marrow and the cartilage to biochemical properties of the cartilage in patients with rheumatoid arthritis (RA).33 patients with RA received 3-T MRI scans of the metacarpophalangeal joints. Two independent methods, (A) the delayed gadolinium enhanced MRI of the cartilage (dGEMRIC, T2-mapping), which was used to assess the biochemical properties of the cartilage; (B) synovitis, osteitis and bone erosions were quantified according to the RA MRI scoring (RAMRIS) method and cartilage thickness (CT), interbone joint space (IBJS, distance between proximal and distal bone surface) and intercartilage joint space (ICJS, distance between proximal and distal cartilage surface) were measured.Biochemical changes of the cartilage, corresponding to low dGEMRIC and high T2 values, were more likely to be seen in joints with decreased IBJS and ICJS as well as decreased CT. For instance, dGEMRIC was directly correlated to the IBJS (p=0.001) and ICJS (p=0.001), whereas T2 mapping was inversely correlated to IBJS and ICJS (both p=0.017). Moreover, the degree of osteitis, and to some extent synovitis, was correlated to biochemical cartilage changes as measured by dGEMRIC (p=0.003) or the T2 mapping (p=0.013). By contrast, bone erosions did not correlate to the degree of biochemical cartilage changes.These data support the concept that synovitis and osteitis may be two main triggers for cartilage damage. Thus, the actual inflammatory state of a joint, but not so much the degree of bone erosion, appears to influence cartilage properties in RA.
EVALuna2:10039